ANALISIS PENGARUH INTERNAL CASH FLOW, INSIDER OWNERSHIP, PROFITABILITAS, KESEMPATAN INVESTASI DAN PERTUMBUHAN PENJUALAN TERHADAP CAPITAL EXPENDITURE (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia) - Aini Farida; Andi Kartika (Faculty of Economic and Business Universitas STIKUBANK, 2016)
The study examines the effect of internal cash flow, insider ownership, profitability, investment opportunity and sales growth on capital expenditure. This research was conducted at the Indonesian Stock Exchange by using a go public manufacturing company as the unit of analysis.Population in this research is manufacturing company listed on the Indonesian Stock Exchange period form 2010 to 2014. The sampling method used purposive sampling. The research sample includes companies that have insider ownership, releasing financial statement, has the completeness of data, used the rupiah currency Relationship and (or) influence between variables is describe by using multiple regression analysis.The result showed that the insider ownership has significant negative effect and investment opportunity has significant positive effect to the capital expenditure. Where as the internal cash flow and sales growth has no significant positive effect, and profitability has no significant negative effect to the capital expenditure.Keywords: Internal Cash Flow, Insider Ownership, Profitability, Investment Opportunity, Sales Growth and Capital Expenditure.